PERAN LEMBAGA KPU DAN BAWASLU DALAM MENGATASI PERMASALAHAN DAFTAR PEMILIH TETAP (DPT) SAAT PEMILIHAN UMUM - Alse Hawana (Fakultas Hukum Universitas Islam Syekh Yusuf, 2022)
As it is known that the level of participation is measured by looking at the number of voters present compared to the number of registered voters. If the validity of the DPT is low or there is a lot of duplicate data, it is invalid then automatically many registered residents are absent. The occurrence of duplicate data in the DPT affects the level of participation. That participation is influenced by the accuracy of population data can be seen in the voter registration method. This research uses literature study. Literature study can study various references and the results of similar previous studies which are useful for obtaining a theoretical basis for the problem to be studied. The question in this research problem is what is the role of the KPU and Bawaslu in overcoming the problem of the fixed voter list at the time of the election. The purpose of this research is to find out and analyze the role of the KPU and Bawaslu institutions in overcoming the problem of the fixed voter list when the election is about to take place. Every time a legislative election, presidential election or regional head election is held, one of the KPU's main activities is to make the voter list. Bawaslu has an obligation to oversee the process and results of updating and maintaining voter data on an ongoing basis whose authority is granted by law. Keywords: KPU; Bawaslu; Fixed Voters List ; Election